A genomic and morphometric analysis of alpine bumblebees: Ongoing reductions in tongue length but no clear genetic component. Issue 4 (7th December 2021) - Christmas, Matthew J.; Jones, Julia C.; Olsson, Anna; Wallerman, Ola; Bunikis, Ignas; Kierczak, Marcin; Whitley, Kaitlyn M.; Sullivan, Isabel; Geib, Jennifer C.; Miller‐Struttmann, Nicole E.; Webster, Matthew T.
Abstract: Over the last six decades, populations of the bumblebees Bombus sylvicola and Bombus balteatus in Colorado have experienced decreases in tongue length, a trait important for plant‐pollinator mutualisms. It has been hypothesized that this observation reflects selection resulting from shifts in floral composition under climate change. Here we used morphometrics and population genomics to determine whether morphological change is ongoing, investigate the genetic basis of morphological variation, and analyse population structure in these populations. We generated a genome assembly of B . balteatus . We then analysed whole‐genome sequencing data and morphometric measurements of 580 samples of both species from seven high‐altitude localities. Out of 281 samples originally identified as B . sylvicola, 67 formed a separate genetic cluster comprising a newly‐discovered cryptic species ("incognitus"). However, an absence of genetic structure within species suggests that gene flow is common between mountains. We found a significant decrease in tongue length between bees collected between 2012–2014 and in 2017, indicating that morphological shifts are ongoing. We did not discover any genetic associations with tongue length, but a SNP related to production of a proteolytic digestive enzyme was implicated in body size variation. We identified evidence of covariance between kinship and both tongue length and body size, which is suggestive of a genetic component of these traits, although it is possible that shared environmental effects between colonies are responsible. Our results provide evidence for ongoing modification of a morphological trait important for pollination and indicate that this trait probably has a complex genetic and environmental basis.